2023
DOI: 10.1002/htj.22806
|View full text |Cite
|
Sign up to set email alerts
|

Frictional material selection of dry clutch disc based on the weighted factor and finite element methods

Abstract: The main task of the frictional facing of a clutch disc is to transfer the power from the driving to the driven parts. High frictional heat will be generated when the frictional facing comes into contact with the moving surfaces (flywheel and pressure plate). In this research paper, the selection of the frictional-facing material of the clutch disc has been investigated to obtain the optimal thermal behavior of the clutch system. It used five different frictional materials (St37-2, HCC, G95, LUK, and Tiger), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…The results showed that the use of HCC material improves the thermal performance of the dry clutch system. In Qasim M. Doos et al [14], the selection of the frictional-facing material of the clutch disc was investigated to obtain the optimal thermal behavior of the clutch system numerically. It used five different frictional materials ie St37-2, HCC, G95, LUK, and Tiger.…”
Section: Frictional Facingmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that the use of HCC material improves the thermal performance of the dry clutch system. In Qasim M. Doos et al [14], the selection of the frictional-facing material of the clutch disc was investigated to obtain the optimal thermal behavior of the clutch system numerically. It used five different frictional materials ie St37-2, HCC, G95, LUK, and Tiger.…”
Section: Frictional Facingmentioning
confidence: 99%
“…Based on what was presented in the introduction section, it is clear that there is a significant effect of high-temperature levels on the behavior and performance of the friction clutch system. Where the thermal effect will cause various types of issues and failures in parts of the clutch system [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16]. Figure 9 summarizes the main trouble/ failure that happened in the frictional facing/ lining of the clutch system, flywheel, and pressure plate due to the thermal effect (high temperature).…”
Section: Materials and Experimental Proceduresmentioning
confidence: 99%